2010
DOI: 10.4141/cjps10009
|View full text |Cite
|
Sign up to set email alerts
|

Volunteer wheat (Triticum aestivum L.) competition in corn (Zea mays L.)

Abstract: . 2010. Volunteer wheat (Triticum aestivum L.) competition in corn (Zea mays L.). Can. J. Plant Sci. 90: 919Á924. Volunteer winter wheat (Triticum aestivum L.) is a sporadic weed found in corn (Zea mays L.) fields across southern Ontario. Eight trials were conducted over a 2-yr period (2006 and 2007) at four locations to determine the competitiveness of volunteer winter wheat in corn. A soft red winter wheat cultivar (Pioneer 25R47) was seeded at each location at densities of 0 to 30 seeds m (2 late in the fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Some years later, Wilson et al. (2010) found a 5% yield decrease in corn ( Zea mays L.) with volunteer wheat densities of approximately 5.5 plants m –2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some years later, Wilson et al. (2010) found a 5% yield decrease in corn ( Zea mays L.) with volunteer wheat densities of approximately 5.5 plants m –2 .…”
Section: Discussionmentioning
confidence: 99%
“…Marshall et al (1989) reported that volunteer wheat at 30 plants m -2 caused a 17% yield reduction in rapeseed (Brassica napus L.) and Friesen et al (1990) with the same volunteer wheat density found a flax (Linum usitatissimum L.) yield reduction of 51% on average. Some years later, Wilson et al (2010) found a 5% yield decrease in corn (Zea mays L.) with volunteer wheat densities of approximately 5.5 plants m -2 . In this study, when the yield supplied by the volunteer wheat was not considered, an average volunteer density of 120 heads m -2 (30 plants m -2 assuming four heads plant -1 ) reduced the yield of seeded wheat an average of 13% among the four fields (Figure 1a).…”
Section: Competitionmentioning
confidence: 99%